Globalisasi dan Implikasinya Terhadap Pelindungan serta Pemanfaatan Kekayaan Intelektual Budaya Tradisional dalam Sektor Pariwisata - Arabiyah, Syarifah; Prabowo, Agung Dwi (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
Intellectual property (IP) protection is the important thing in protecting and utilizing the creations of human ideas. Creations can take many forms including inventions, arts and literaries, industrial designs, and others. IP not only regulates individual ownership but also concerns about communal ownership based on local culture. Nowdays, globalization affects the protection and utilization of IP including local culture. As one of important factor in global business, recognition of IP based on local culture has the opportunity to become a new advantage for the tourism sector in globalization era especially for tourism which managed by local communities. For example is the utilization of digital technology for tourism business based on local cultural IP which is useful for improving community welfare in terms of economic and moral benefits. the business will be globalized and opportunities for equitable use of local cultural IP will be widely opened. Digitalization will also facilitate the protection and utilization of local cultural IP in order to gain global recognition easily and make tourism sector based on local cultural IP to be more competitive with other countries in order to attract the attention of foreign tourists. This article is a normative with non judicial case study. The methods are statute and conceptual approaching method. The purpose of this article is to determine the form of protection and utilization of IP based on local culture that is ideal for tourism sector in the era of globalization.